2011
DOI: 10.1164/rccm.201103-0374oc
|View full text |Cite
|
Sign up to set email alerts
|

Hemolytic Phospholipase C Inhibition Protects Lung Function during Pseudomonas aeruginosa Infection

Abstract: We have directly linked production of a single virulence factor in P. aeruginosa with effects on lung function, and demonstrated that the inhibitor miltefosine protects lung function from PlcHR-dependent surfactant dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(85 citation statements)
references
References 69 publications
4
77
0
4
Order By: Relevance
“…Previous work has shown that PlcH degrades phospholipids in host membranes and in lung surfactant both in vivo and in vitro (8,41). Furthermore, we recently reported that the recovery of WT P. aeruginosa was 40-fold greater than that of ⌬plcHR mutant cells after oropharyngeal infections of the mouse lung with 10 6 CFU of P. aeruginosa (42). To understand the role of PlcH, if any, in colonization of and growth in the lung, we examined P. aeruginosa WT and ⌬plcHR mutant cells in an airway epithelial cell colonization assay.…”
Section: Resultsmentioning
confidence: 86%
“…Previous work has shown that PlcH degrades phospholipids in host membranes and in lung surfactant both in vivo and in vitro (8,41). Furthermore, we recently reported that the recovery of WT P. aeruginosa was 40-fold greater than that of ⌬plcHR mutant cells after oropharyngeal infections of the mouse lung with 10 6 CFU of P. aeruginosa (42). To understand the role of PlcH, if any, in colonization of and growth in the lung, we examined P. aeruginosa WT and ⌬plcHR mutant cells in an airway epithelial cell colonization assay.…”
Section: Resultsmentioning
confidence: 86%
“…To test whether GbdR was necessary for the transcriptional changes of previously unverified transcripts, we grew cells as described for the microarray preparation, except that wild-type (WT) and ⌬gbdR mutant cells were exposed to pyruvate or 1 mM choline in MOPS pyruvate medium for 3 h. RNA was prepared as described for the microarray experiments. cDNA was generated using Superscript III (Invitrogen) and the 5=-NSNSNSNSNS-3= primer as described previously (19). Quantitative PCR (qPCR) was performed using the Luminaris color HiGreen fluorescein qPCR master mix (Thermo Scientific) with the primers described in Table S1 in the supplemental material.…”
Section: Methodsmentioning
confidence: 99%
“…Bacteria commonly produce secreted phospholipases C and/or D, which liberate phosphorylcholine or choline from choline phosphate-containing phospholipids and sphingolipids, respectively (32,33). These phospholipases are often considered virulence factors, when studied in opportunistic pathogens (reviewed in reference 33), that can alter bacterial survival, cause cell damage, induce inflammatory cytokine production, and suppress antibacterial responses of innate immune cells (34)(35)(36)(37). However, they could also be categorized as choline/nutrient acquisition systems beneficial for niche survival (38), with the side effects of host cell damage and potential hemolysis.…”
Section: Distribution and Biological Roles Of Choline And Gbmentioning
confidence: 99%